PENGARUH ALAT PERMAINAN EDUKATIF PUZZLE ANGKA TERHADAP PENINGKATAN MOTORIK HALUS ANAK PRASEKOLAH USIA 4-6 TAHUN DI RA TARBIYATUL ULA SUMBERKARE: PENGARUH ALAT PERMAINAN EDUKATIF PUZZLE ANGKA TERHADAP PENINGKATAN MOTORIK HALUS ANAK PRASEKOLAH USIA 4-6 TAHUN DI RA TARBIYATUL ULA SUMBERKARE - Musyarrofah; Iis Hanifa; Homsiatur Rohmatin (ASSYIFA : Jurnal Ilmu Kesehatan, 2023)
Fine motor development in children has an important role in growth and development in children. Poor fine motor development in children if not treated will affect the child's development process. The purpose of this study was to analyze the Effect of Number Puzzle Educational Game Tools (Ape) on Fine Motor Improvement in Preschool Children Aged 4-6 Years at Ra Tarbiyatul Ula Sumberkare. The design of this study was a Pre Experiment with a One Group Pre Test Post Test Design approach. This study included 38 participants, all of them were youngsters aged 4-6 years old at RA Tarbiyatul Ula. Using the entire sampling approach, the sample consists of all children aged 4-6 year. A checklist observation sheet and SOP for the number puzzle game were utilized as instruments. The study's findings before receiving an educational number puzzle game, 16 respondents began to develop after receiving an instructional number puzzle game, 26 people developed as expected. Based on the Wilcoxon statistical test, it is known that the P value is 0.000 with α 0.05 . Because the significance value is <α, then H0 is rejected and H1 is accepted, indicating that the number puzzle educational game tool has an effect on the fine motor abilities of preschoolers aged 4-6 years at RA Tarbiyatul ula.